Jian-Pi-Yi-Shen Formula Ameliorates Oxidative Stress, Inflammation, and Apoptosis by Activating the Nrf2 Signaling in 5/6 Nephrectomized Rats - Zhou, Fanyuan; Zou, Xiaohu; Zhang, Jing; Wang, Ziwei; Yang, Yajun; Wang, Dongtao (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is an increasing global public health problem, with high morbidity and mortality. Jian-Pi-Yi-Shen (JPYS) formula is a representative traditional Chinese medicine formula in the treatment of CKD, which is widely used in clinical practice in China. However, the underlying mechanism has not been well elucidated. In the present study, we measured the markers of apoptosis, inflammation, oxidative stress, and nuclear factor erythroid 2–related factor 2 (Nrf2) signaling to investigate the effects of JPYS formula on renal function and fibrosis and its molecular mechanism in an established animal model of 5/6 nephrectomized (5/6Nx) rats. The results demonstrated that the JPYS formula exerted a significant preventive effect on renal dysfunction and fibrosis, based on analysis of correlative parameters such as urinary protein, SCr, BUN, glomerular sclerosis index, and tubulointerstitial fibrosis score and renal histopathology and ultrastructural pathology of CKD rats. JPYS formula also induced downregulation of gene expression associated with fibrosis, such as TGF-β and type I, III, and IV collagen. Moreover, the JPYS formula showed a significant protective effect in suppressing cell apoptosis according to the results of apoptotic indexes, including increased gene expression of Bcl-2, decreased gene expression of Bax, caspase 3, caspase 9, and the number of TUNEL-positive cells. JPYS formula also ameliorated the activation of the NF-κB-mediated inflammatory pathway, as manifested by the downregulation of gene expression of TNF-α, IL-1β, IκBα, NF-κB p65, MCP-1, CXCL1, COX-2, and iNOS in the kidney. Our evidence also suggested that the JPYS formula ameliorates oxidative stress by promoting antioxidant function according to antioxidant index indicators as an indicator of GSH, SOD, CAT, and GPx and abating excessive accumulation of the reactive oxygen species biomarkers, including ROS, TBARS, 8-oxo-dG, and MDA. The data also suggested that the JPYS formula reversed the downregulation of HO-1 and Nrf2 level and upregulation of Keap1 expression. Together, our data highlighted that the JPYS formula relieved renal oxidative injury mediated by activation of Nrf2 signaling by inhibiting inflammation and apoptosis in CKD rats.